2015
DOI: 10.1620/tjem.237.219
|View full text |Cite
|
Sign up to set email alerts
|

Greater Reduction of Balance as a Result of Increased Plantar Fascia Elasticity at Ovulation during the Menstrual Cycle

Abstract: One of the sexual hormones, estrogen, increases elasticity of human connective tissue such as the anterior cruciate ligament during the menstrual cycle in women. In the present investigation, the plantar fascia was investigated to see if there is a difference in elasticity with the menstrual cycle. Fifteen young healthy females in the age range of 18-35 years old with a regular menstrual cycle were tested twice throughout one full menstrual cycle; once during the early follicular phases and once at ovulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 57 publications
2
44
0
1
Order By: Relevance
“…8,18 Greater postural sway during ovulation than in the early follicular phase (menstruation) has been reported. 22 This could be explained by the complex interaction between knee and ankle laxity as noted earlier. Ericksen and Gribble 23 found less ankle stability in women than in men but reported no effects of the menstrual cycle.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…8,18 Greater postural sway during ovulation than in the early follicular phase (menstruation) has been reported. 22 This could be explained by the complex interaction between knee and ankle laxity as noted earlier. Ericksen and Gribble 23 found less ankle stability in women than in men but reported no effects of the menstrual cycle.…”
mentioning
confidence: 83%
“…The validity and reliability of this force platform were established in previous studies. 22,30 Four stainless steel bars, each with 4 strain gauges (model FLA-6, 350-17; Tokyo Sokki Kenkyujo Co, Ltd, Tokyo, Japan), were mounted at the 4 corners under the platform. The output of the 4 Wheatstone strain gauge bridges was amplified by a low-level biopotential amplifier (model M35; BIOPAC Systems, Inc, Goleta, CA) and digitized through a 24-bit A/D converter.…”
Section: Instrumentationmentioning
confidence: 99%
“…However, only a few studies that provide evidence on ankle stability have been conducted (Hosea et al 2000;Trimble et al 2002;Petrofsky and Lee 2015;Silbernagel et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To detect relaxin receptor 1 (RXFP1) and estrogen receptor-alpha (ERα), dewaxed sections were treated with Tris-EDTA pH 9.0 buffer for 15 min at 95°C, rinsed in water, and then washed in PBS. Isolated cells from fascia were plated (200 cells/mm 2 in 24-multiwells containing a glass coverslip) and allowed to attach for 48 h at 37°C. Cells were then washed in PBS, fixed for 10 min with 2% paraformaldehyde in PBS pH 7.4 and then washed three times in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…1 demonstrated that type I collagen in the arcus tendineous fasciae pelvis decreased in post-menopausal women, possibly compromising the tissue’s tensile strength and increasing susceptibility to anterior vaginal wall prolapse. Petrofsky and Lee 2 demonstrated plantar fascia elasticity changes during the menstrual cycle, suggesting a possible role of the sexual hormones in increasing the elasticity of human connective tissue. In 1984, a prospective study by Möller-Nielsen and Hammar 3 showed that women soccer players were more susceptible to traumatic injuries during premenstrual and menstrual periods with respect to other periods of their menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%